THE DEVELOPMENT OF SOYBEAN PLANTS DEPENDS ON THE FERTILIZER SYSTEM - Марініч, Любов; Радочіна, Ольга (SWorldJournal, 2024)
Topicality. Fertilization systems are an important element in the technology of growing soybeans, and many years of culture studies prove that soybeans are quite demanding of this factor. To date, the response of modern soybean varieties to the complex ap